Gender Role in Environmental Protection in Developing Countries : Case Study Indonesia - Primadiana Yunita (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2019)
The relationship of women in the environment is something that cannot be separated. In their daily lives the role of women tends to be closer to the environment, such as the availability of clean water, household waste management, caring for plants, horticulture, agroforestry, etc.The lack of understanding of women and the limited access of women to various information about the environment that makes women potentially contribute to damage the environment. In terms of its impact, women also become more vulnerable to pollution and environmental damage.In more extensive cases, namely climate change, women are also the most vulnerable.The problem is that various facts about the impact of climate change on women have not been accompanied by an awareness of the importance of involving women as "forgotten" parties in various discussions on climate change. This paper contains an analysis of the role of women as actors in policy making related to issues of environmental change.